The role of the PPAR-FABP signalling axis in inflammatory response in dorsal root ganglia - Mat Harun, Noraihan (2019)
The peroxisome proliferator-activated receptors (PPARs) are ligand-regulated transcription factors which are members of the nuclear receptor group. They induce transcription of multiple genes encoding proteins involved in fatty acid and glucose metabolism, as well as cell differentiation and inflammation. Fatty acids are important for mammals not only as nutrient molecules but also as mediators for intracellular signalling. They are highly hydrophobic and need a transporter system like fatty acid binding proteins (FABPs) to carry them across the cytoplasm and nucleus. FABPs are small cytosolic proteins capable of sequestering hydrophobic ligands and delivering them to a variety of target proteins and receptors within cells such as PPARs. The type of ligand bound by the FABP and the target receptor can influence a range of cellular signalling cascades. For example, PPAR lipid ligands known to be bound by FABPs can exhibit an anti-nociceptive effect in animal models of pain. The main aim of this thesis was to study the role of the FABP and PPAR signalling axis in the inflammatory response in dorsal root ganglia (DRG) as the first relay point of the pain pathway. DRG are a collection of neuronal cell bodies at the peripheral nervous system. Each neuronal body is surrounded by satellite glial cells forming a distinct functional unit. The subpopulation distribution of the different types of FABPs and PPARs in rat DRG sections was determined by in situ hybridization (ISH) and TaqMan qPCR. Protein-protein interactions of FABPs and PPARs were studied by Bimolecular fluorescence complementation (BiFC) assays. Furthermore, the differential effects of PPAR agonists on inflammatory genes induced by lipopolysaccharides (LPS) or flagellin in rat DRG cultures were investigated by TaqMan Low Density Array (TLDA). All PPAR isotypes together with FABP5, FABP7 and FABP8 can be detected in both neuronal and glial cells of DRG. Further analysis by ISH and TaqMan qPCR showed that PPARα was expressed significantly higher in glial cells, while PPARβ and PPARγ were expressed more in neuronal cells. FABP5 expression was higher in neuronal cells, FABP7 expressed almost equally in both cells and FABP8 expression was significantly higher in glial cells. Furthermore, protein-protein interaction assays between FABPs and PPARs by BiFC showed that FABP5 interacts with PPARα and PPARβ, and FABP8 interacts with all the PPAR isoforms. The protein-protein interaction was augmented in the presence of a respective PPAR agonist. Subsequently, the TLDA study showed that most of the inflammatory genes were inhibited by all three PPAR agonists in LPS-induced inflammation. Meanwhile, in flagellin-induced inflammation, PPARα agonist was more likely to be effective in suppressing some of the inflammatory gene expression. In addition, we also found that Toll-like receptor 4 (TLR4) and TLR5 were expressed in rat DRG, in which, TLR4 expression was higher in neuronal cells and TLR5 was higher in glial cells. Therefore, this might suggest that TLR4 activation by LPS is probably primarily in neuronal cells, thus the inflammatory genes were suppressed by the three PPARs that are all expressed in the neuronal cells. On the other hand, PPARα and TLR5 are expressed at high levels in glial cells, and there is a possibility that inflammatory mediators from flagellin-mediated activation of TLR5 on glial cells can mainly be suppressed by PPARα.